STUDY OF FERMENTATION OF LEMONGRASS WASTE (Cymbopogon nardus), RICE BRAN AND CORN FRACTION WITH Pleurotus ostreatus ON FIBER FRACTION AND DIGESTION OF DRY MATTER, ORGANIC MATTER, AND CRUDE PROTEIN - Nur, Yuliaty Shafan; Arfa`i, Arfa`i (Jurnal Ilmu Ternak Universitas Padjadjaran, 2025)
Lemongrass waste can be used as an alternative feed to replace grass for ruminant livestock, but it has a high crude fiber content. Therefore, it is necessary to handle and process lemongrass waste. This study examines the effect of inoculum dose and fermentation time of lemongrass waste (Cymbopogon nardus) with Pleurotus ostreatus on fiber fraction, dry matter digestibility, organic matter, crude protein. The research method is a randomized block design consisting of 6 treatments of lemongrass waste with rice bran and corn shards and 3 replications as a group. The inoculum dose is 6%, 9% and 12% and the fermentation time is 14 and 21 days. The parameters are fiber fraction (NDF, ADF, Hemicellulose, Cellulose, dry matter digestibility of organic matter, crude protein. Data were processed using Analysis of Variance (ANOVA) and differences between treatments were tested using Duncan Multiple Range Test (DMRT). The results of the analysis of variance showed that the treatment had a very significant effect (P< 0.01) on NDF, ADF and Hemicellulose and a significant effect (P < 0.05) on dry matter digestibility and organic matter digestibility but not significant (P>0.05) on crude protein digestibility. It was concluded that the best dose in this study was 12% and a fermentation time of 21 days with NDF content of 62.33%, ADF 48.16%, cellulose 30.38%, hemicellulose 14.16%, KcBK 58.01%, KcBO 58.24% and KcPK 50.16% in-vitro.